ANALYSIS OF SUSTAINABILITYPEATLAND IN AGROECOLOGY OIL PALM PLANTATION - Sowondo dkk (Jurnal Rekayasa Lingkungan)
This research was based on the damages of peatlands. Peatland was potential to be developed as plantation. The objective of the research was to examine sustainability index of peatlands management on agroecology palm oil plantations at Bengkalis-Riau. The point location was determinated with purposif sampling as palm oil activited and which were peatland physiography at marine and brackish peat. The data collected using desk study and field survey. The sustainable measurements were conducted on the dimensions of ecological, economic, socio-culture, infrastructure and technology, law and institutional. Multi Dimensional Scaling (MDS) it’s called Rap-Insus-Landmag (Rapid Appraisal–Indeks Sustainability of Land Management) was used evaluatedsustainability of peatland management on agroecology palm oil plantation. The results of this study indicated that marine peat and brakish peat sustainability for five dimension (ecology, economic, socio-culture, infrastructure and technology, law and institutional) on the existing condition i.e. ecological dimension less sustainable (49,14 % and 46,60 %), economic moderate sustainable (69,30 % and 64,7 %), socio-culture moderate sustainable (52,32 % and 54,47 %), infrastructure and technology moderate and less sustainable (51,15 % and 49,64), law and institutional moderate sustainable (50,33 %and 56,99 %). Therefore, sustainability peatlands of management on groecology oil palm plantations have category less-to-moderate at the Bengkalis-Riau.keywords : peatland, sustainable, palm oil plantation